Electrochemical Properties of a Gold Nanoseed Particle‐Attached Nickel Electrode. Issue 4 (12th February 2015) - Uemoto, Takahiro; Nakayama, Yosuke; Chen, Xiaomei; Chang, Gang; Oyama, Munetaka; Rees, Neil V.
Abstract Gold nanoseed particles (AuNSPs) of ca. 3.5 nm were attached on a Ni disk electrode, and the electrochemical properties of the thus‐prepared AuNSP‐attached nickel (AuNSP/Ni) electrode were investigated. As a remarkable effect of AuNSPs, cyclic voltammograms of Fe(CN)<alternatives> <![CDATA[4- 6]]> <inline-graphic xlink:href="ark:/27927/pgjj6r6bmb" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> recorded with an AuNSP/Ni electrode was reversible and almost identical to those recorded with an Au disk electrode, while a reversible response was not observed with a Ni disk electrode. The similar tendency was observed for the electrochemical oxidation of uric acid and glucose. Also, AuNSPs was proved to suppress the redox reactions of the Ni electrode in alkaline solutions.